Formation of the young compact cluster GM 24 triggered by a cloud–cloud collision. (6th January 2018) - Fukui, Yasuo; Kohno, Mikito; Yokoyama, Keiko; Nishimura, Atsushi; Torii, Kazufumi; Hattori, Yusuke; Sano, Hidetoshi; Ohama, Akio; Yamamoto, Hiroaki; Tachihara, Kengo
Abstract: High-mass star formation is an important step which controls galactic evolution. GM 24 is a heavily obscured star cluster including a single O9 star with more than ∼100 lower-mass stars within a 0.3 pc radius toward ( l, b ) ∼ (350^°_.5, 0^°_.96 ), close to the Galactic mini-starburst NGC 6334. We found two velocity components associated with the cluster by new observations of 12 CO J =2–1 emission, whereas the cloud was previously considered to be single. We found that the distribution of the two components of 5 km\: s −1 separation shows complementary distribution; the two fit well with each other if a relative displacement of 3 pc is applied along the Galactic plane. A position–velocity diagram of the GM 24 cloud is explained by a model based on numerical simulations of two colliding clouds, where an intermediate velocity component created by the collision is taken into account. We estimate the collision time scale to be ∼Myr in projection of a relative motion tilted to the line of sight by 45°. The results lend further support for cloud–cloud collision as an important mechanism of high-mass star formation in the Carina–Sagittarius Arm.